Anatomy of Indian energy policy: A critical review. Issue 11 (2nd November 2017) - Kumar, G. Sathis
ABSTRACT: Energy becomes essential ingredient, for not only the development of different economic sectors, but also for enhancing the health and wealth of human being. At the macro level, significance of energy can be measured in terms of energy consumption (by different sectors), energy production (by different sources), energy import and energy export, energy pricing, energy efficiency, energy conservation and energy distribution. Whereas, at the micro level, identifying, assessing and listing the production (supply) and consumption (demand) of energy, and distribution of energy in end-use sectors, are the critical impediments for energy planning and energy management. Thus, for achieving faster development and growth, economies essentially produce and consume more energy, because energy consumption and production are considered as an index of economic development. In contrast, environmentalists believe that the energy indicators reflect the environmental damage and produce different forms of pollution. In this context, welfare economists are of different views and they point out that energy efficiency in terms of energy intensity and energy equity in terms of equality distribution of energy has to be taken into consideration for creating and promoting welfare state. With this background, the authors – micro economists – from countryside have taken a felt need initiatives to look into energy policy initiatives of Government of India (GoI). In spite of several initiatives taken both at the macro and micro level by GoI's organs like Ministry of Power (MoP), Ministry of Coal (MoC), Ministry of Petroleum and Natural Gas (MoPNG), Ministry of New and Renewable Energy Sources (MNRES), the energy economy of India is still in critical stage and energy crises are the order of the day in Indian economy which reflects in almost all development sectors.